Structure and Mechanical Property of Melt-Drawn Oriented PLA Ultrathin Films - Li, Yunpeng; Xin, Rui; Wang, Shaojuan; Guo, Zhixin; Sun, Xiaoli; Ren, Zhongjie; Li, Huihui; Li, Li; Yan, Shouke (Macromolecules, 2021)
Ultrathin poly(lactic acid) (PLA) films have been prepared by a melt-draw technique, and their structures and mechanical properties have been studied by atomic force microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, and tensile test. It is found that the melt-drawn PLA films consist of highly oriented granular α microcrystallites. The draw rate and temperature exhibit a synergistic effect on regulating the structures, including crystallinity and chain orientation, of the melt-drawn films. Post-thermal annealing leads to a structure reorganization from granular into lamellar structures with enhanced crystallinity up to about 55%. It also increases the chain orientation in the amorphous region, while the orientation status of chains in the crystalline phase remains almost unchanged because its orientation function in the as-prepared samples already close to 1. Mechanical tests of the melt-drawn poly(l-lactic acid) films illustrate a tremendous enhancement in mechanical properties of oriented PLA films compared to their nonoriented counterpart. The highest Young’s modulus and tensile strength achieved for the sample prepared at 180 °C under a draw rate of 45 cm/s are about 1.3 and 2.5 times higher than those of its nonoriented counterpart.